Development of porous alumina membranes for treatment of textile effluent. Issue 6 (1st February 2016) - Silva, Késia Karina O.S.; Paskocimas, Carlos A.; Oliveira, Fernando R.; Nascimento, José H.O.; Zille, Andrea
Abstract: Ceramic porous membranes sintered at two different temperature using polyvinyl alcohol and ethylene glycol as binders, and composed of two types of α-alumina with different particle sizes were investigated for the microfiltration of a textile effluent containing indigo dye, auxiliaries, heavy metals, oils, and solids. The physicochemical properties of the membranes and effluent were evaluated. X-ray diffraction, energy dispersive X-ray fluorescence spectroscopy, differential scanning calorimetry, and thermogravimetric analysis confirm that the thin membrane is composed of high crystalline and pure α-alumina. Scanning electron microscopy observation indicates that the membranes have smooth porous surface making it suitable for microfiltration applications. The membrane sintered at 1, 450°C exhibited higher water absorption (WA) and apparent porosity than that sintered at 1, 475°C. The apparent specific gravity and flexural strength are in inverse correlation with the WA due to the enhanced densification of the membranes. The filtered effluent was evaluated using a membrane with an average pore size of 0.4 μm and a total porosity of 29.6%. The average values of rejection were 90% for color, 93% for suspended solids, 95% for turbidity, 60% for metals, and 73% for chemical oxygen demand. These results demonstrate that low-cost ceramic alumina membranes are a very promising advanced treatment for textile industrial effluents.